2019
DOI: 10.1371/journal.pone.0218715
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic tendons of the pectoralis minor muscle as cause for shoulder pain and motion inhibition—Explaining clinically important variabilities through phylogenesis

Abstract: OJECTIVE Clinical consequences of ectopic tendons of the pectoralis minor muscle (PMM) for shoulder pain and range-of-motion limitation have been demonstrated. For better understanding the existence of such ectopic tendons, a phylogenetic hypothesis is proposed. METHODS Forty-five shoulders of anatomical specimens were dissected and examined. Insertions areas of PMM were measured and occurring aberrant tendons were identified. Their relationship with the coracohumeral l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…They reported a coracoid insertions size of the ligament of 66.5 ± 23.8 mm 2 and a humeral insertion size of 68.3 ± 18.4 mm 2 . Also, Schwarz and Hirtler 29 in their paper on the ectopic tendons of the pectoralis minor muscle measured the coracoid insertion area of the CHL, which was overall 56.5 ± 36.3 mm 2 , ranging from 54.9 ± 34.4 mm 2 in their group without variation to 66.31 ± 33.8 mm 2 in their group with variation (exemplary image of an ectopic tendon of the pectoralis minor muscle may be found as supplementary material). Although the results of this study showed generally smaller insertion sites compared to the two prior publications, this mainly reflects the interindividual variability of this anatomical structure, which is also mainly supported by the sex-difference reported.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…They reported a coracoid insertions size of the ligament of 66.5 ± 23.8 mm 2 and a humeral insertion size of 68.3 ± 18.4 mm 2 . Also, Schwarz and Hirtler 29 in their paper on the ectopic tendons of the pectoralis minor muscle measured the coracoid insertion area of the CHL, which was overall 56.5 ± 36.3 mm 2 , ranging from 54.9 ± 34.4 mm 2 in their group without variation to 66.31 ± 33.8 mm 2 in their group with variation (exemplary image of an ectopic tendon of the pectoralis minor muscle may be found as supplementary material). Although the results of this study showed generally smaller insertion sites compared to the two prior publications, this mainly reflects the interindividual variability of this anatomical structure, which is also mainly supported by the sex-difference reported.…”
Section: Discussionmentioning
confidence: 96%
“…This is especially important when applying imaging techniques such as MRI in an anatomical setting. As no additional imaging was performed, tissue quality for dissection was acceptable, especially as previous studies also pointed out the disadvantage of formalin-phenol fixation in terms of evaluating ligaments and tendons 29 . Particularly the distinction of different tissue layers was not affected by cryo-preservation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether this is due to different specimen characteristics or the different fixation methods (fresh‐frozen vs. formalin‐ethanol) cannot be finally clarified. However, Schwarz and Hirtler ( 2019 ) were able to show that the frequency distribution of aberrant pectoralis minor tendons are similar between Caucasians and Mongolians, which might predict similarities in the supraspinatus muscle as well. Our results on the infraspinatus muscle are in accordance with previous results (Mochizuki et al, 2008 ).…”
Section: Discussionmentioning
confidence: 98%
“…A instance of bilateral capsular insertion of a section of PMi was described by Patten [22]. PMi was inserted into the upper part of the glenoidal lip and the surrounding capsule, according to reports [23].…”
Section: Discussionmentioning
confidence: 99%